MEKANISME GOOD CORPORATE GOVERNANCE DAN TRANSPARANSI PERUSAHAAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Damara Putri Utami; Willy Sri Yuliandari; Muhamad Muslih (JRAK, 2017)
The level of CSR disclosure in Indonesia is still low because of a lack company commitment to do the CSR activities. The implementation of GCG indicated can support the implementation of CSR in an enterprise because there is a relationship between GCG and CSR. The purpose of this study is to examine the influence of GCG mechanism (proportion of independent commissioners, the number of audit committee, managerial ownership) and corporate transparency, either simultaneously or partially on CSR disclosure. This study uses listed company in SRI KEHATI Index at Indonesia Stock Exchange in 2013-2015 as a population. The sample selection technique using purposive sampling and analytical method using panel data regression. The result of this study shows that GCG mechanism and corporate transparency simultaneously have significant affect on CSR disclosure. Partially shows that proportion of independent commissioners and corporate transparency have significant affect with negative direction on CSR disclosure, while the number of audit committee and managerial ownership has no affect on CSR disclosure.